Plasma Tie2 is a tumor vascular response biomarker for VEGF inhibitors in metastatic colorectal cancer - Gordon C. Jayson (Nature Portfolio, 2018)
Identification of response biomarkers is a key step towards the development of personalised care. Here, Jayson et al. identify plasma Tie2 as a biomarker for the response of the tumor vasculature to anti-angiogenics in patients with metastatic colorectal cancer, suggesting that monitoring Tie2 levels may help guide therapy in the clinics.